﻿The Global Scaling Gap: Why Strategic Clarity Is Crucial in the Age of AI - Wright, Nataliya (MIT Sloan Management Review, 2026)
Digital platforms and generative AI have made it easier than ever for startups anywhere to access global talent and markets, but companies outside major hubs still struggle to scale. The culprit isn’t a lack of technology — it’s a lack of strategic focus. Research points to two traps companies fall into, but applying a practical framework can help them compete on their own terms, regardless of location.